Living in two cultures: the socio-cultural situation of migrant workers and their families - Parris, Ronald G. (Unesco, 1982)
Living in two cultures : the everyday world of migrant workers / Aaron V. Cicourel -- The ghetto of the soul : socio-cultural factors of language training programmes for migrant workers in Norway /Carolyn Swetland -- The unguided learning of German by Spanish and Italian workers / Norbert Dittmar -- Changing one's country means changing one's flag / Maurizio Catani -- Joint theoretical and methodological commentary / Maurizio Catani, Norbert Dittmar, and Carolyn Swetland -- Introduction : research on a "lost generation" / Michel Oriol -- Limitation of births among Yugoslav women migrants in France, the Federal Republic of Germany, and Sweden / Mirjana Morokvasic -- Personal, familial, and societal impacts of Turkish women's migration to Europe / Ayse Kudat -- Transpositions and reinterpretations of the traditional female role in an immigration situation / Sossie Andizian and Jocelyne Streiff -- Epilogue : living in two cultures : some sociological considerations / Dean Harper